Writing for Change An Advanced ELL Resource - Poblet, Inés (Open textbook library., 2021)
This book has been a part of my pandemic journey with a goal of building English language learner resources, gathering up what I have learned about anti-racist, culturally responsive, and decolonization approaches. I know that I have not nearly met this goal in this single resource and that there is so much more to do. I am simply starting on the collective path and am so humbled to join fellow colleagues in the work of rewriting the myths and false narratives of our field. This goes well beyond one specific discipline. It is a call to all educators and all institutions to choose love in action, to choose change. This OER text includes the following: an introduction to creating a collectivist culture to support learning models and activities about multiple ways of organizing ideas in an essay. short readings and discussion highlighting the work of community organizers, activists, and social justice movements writing prompts that ask learners to synthesize, reflect on, and connect to the topics projects inviting learners to apply the content to their community environment additional resources offering multiple modalities for further learning including videos, articles, and podcasts a contrastive and multilingual approach to exploring grammar patterns to support writing